Nudge management: Applying behavioural science to increase knowledge worker productivity - Philip Ebert; Wolfgang Freibichler (Journal of Organization Design, 2017)
Knowledge worker productivity is essential for competitive strength in the digital century. Small interventions based on insights from behavioural science makes it possible for knowledge workers to be more productive. In this point of view article, we outline and discuss a new management style which we label nudge management.
Keywords: 650; Knowledge worker; Productivity; Management control; Nudge theory; Motivation; Choice architecture; Behavioural science; Behavioural economics